2015
DOI: 10.1155/2015/138965
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mechanical and Physical Behaviour of Hybrid GFRP

Abstract: The paper discusses the mechanical and physical behaviour of hybrid glass fibre reinforced plastic (GFRP). Hybrid GFRP was fabricated by three different types of glass fibre, namely, 3D, woven, and chopped, which were selected and combined with mixture of polyester resin and hardener. The hybrid GFRP was investigated by varying three parameters which were the composite volume fractions, hybrid GFRP arrangement, and single type fibre. The hybrid GFRP was fabricated by using open mould hand lay-up technique. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The polymers normally used in GFRP can absorb up to 5% water by weight when immersed for long periods, changing the mechanical properties (e.g. reducing static tensile strength of the material by more than 25%) [14]. Water diffuses into the polymer matrix [13] and the multidirectional nature of laminates complicates the fatigue damage mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The polymers normally used in GFRP can absorb up to 5% water by weight when immersed for long periods, changing the mechanical properties (e.g. reducing static tensile strength of the material by more than 25%) [14]. Water diffuses into the polymer matrix [13] and the multidirectional nature of laminates complicates the fatigue damage mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It is further demonstrated that the stacking sequence is insignificant with regards to tensile properties but significantly influence the flexural and compressive properties. Baba et al [56] reported the findings of the mechanical and physical mode of hybrid glass fibre reinforced plastic (GFRP). Hybrid GFRP is formed by three types of glass fibre which are 3D, woven type and chopped type that are mixed with polyester resin as well as a hardener.…”
Section: Tensile Behavior Of Hybrid C/cfrpmentioning
confidence: 99%
“…It was concluded that woven type recorded the highest value of modulus elasticity owing to its stiff and dense geometry as shown in Figure 4. Besides that, the mat interlocking pattern provides advantages for providing anisotropic behaviour [56]. This mechanism improves the fibermatrix interfacial shear strength.…”
Section: Tensile Behavior Of Hybrid C/cfrpmentioning
confidence: 99%
“…However, the research on the potential of using carbon fibre reinforced polymers (CFRP) in tidal blade design [9; 10] is ongoing [11]. The polymers normally used in GFRP can absorb up to 5% water by weight when immersed for long periods and this can reduce the tensile strength of the material more than 25% [12]. Material properties and design impact the life expectancy, and hence energy production from tidal turbines [13].…”
Section: Composite Tidal Turbine Bladesmentioning
confidence: 99%
“…GFRP tends to absorb a small amount of water, typically less than 5% [12]. The water diffuses into the polymer matrix, changing its mechanical properties.…”
Section: Effects Of Water Saturationmentioning
confidence: 99%